Hippocampal plasticity during the progression of Alzheimer's disease. (19th November 2015) - Mufson, E.J.; Mahady, L.; Waters, D.; Counts, S.E.; Perez, S.E.; DeKosky, S.T.; Ginsberg, S.D.; Ikonomovic, M.D.; Scheff, S.W.; Binder, L.I.
Highlights: Hippocampal plasticity in AD. Molecular plasticity in AD. Hippocampal vulnerability in AD. Abstract: Neuroplasticity involves molecular and structural changes in central nervous system (CNS) throughout life. The concept of neural organization allows for remodeling as a compensatory mechanism to the early pathobiology of Alzheimer's disease (AD) in an attempt to maintain brain function and cognition during the onset of dementia. The hippocampus, a crucial component of the medial temporal lobe memory circuit, is affected early in AD and displays synaptic and intraneuronal molecular remodeling against a pathological background of extracellular amyloid-beta (Aβ) deposition and intracellular neurofibrillary tangle (NFT) formation in the early stages of AD. Here we discuss human clinical pathological findings supporting the concept that the hippocampus is capable of neural plasticity during mild cognitive impairment (MCI), a prodromal stage of AD and early stage AD.